Comparison of Intraoperative Intravenous Ibuprofen versus Intravenous Paracetamol for Post-Operative Pain Relief in Patients Undergoing Laparoscopic Cholecystectomy - Tariq, Waqas; Sarfaraz, Ahmed; Rafique, Ahmad; Sultan khan, Muhammad Asad; Tariq, Hamza Bin; Buland, Khalid (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare intraoperative intravenous Ibuprofen versus intravenous Paracetamol for post-operative pain relief in patients undergoing laparoscopic cholecystectomy.Study Design: Quasi-experimental study.Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Feb to Nov 2021.Methodology: The study was conducted on 400 patients who underwent laparoscopic cholecystectomy during the study period. Patients were randomized into two groups. Group A received intravenous Ibuprofen, while Group B received intravenous Paracetamol during the surgical procedure. The pain at the surgical site was recorded on the visual analog scale (VAS) at 2 hours and 6 hours after the surgical procedure. The difference in post-operative pain and the requirement of opioid analgesia was compared in both groups via the chi-square test.Results: Out of 400 patients randomized into two groups, 198(49.5%) were categorized into Group A, and 202(50.5%) were categorized into Group B. 290(72.5%) were female, while 110(27.5%) were male. The mean age of patients who underwent laparoscopic surgery in our study was 40.24±7.69 years. Patients who received intravenous Ibuprofen had more chances of not having significant postoperative pain at 02 and 06 hours after the surgery as compared to those who received intravenous Paracetamol (p-value